THE PROBLEM OF CORRUPTION OF BASIC SCIENTIFIC INVESTIGATIONS IN PARTICULAR: FORMAL-ETHIC AND ECONOMIC ASPECTS - V. O. Lobovikov (Образование и наука)
The aim of the paper is to carry out historical-philosophical andlinguistic analysis of ethical and metaphysical doctrine of Aristotle on corruption in general; to discuss of formal-ethical view on the problem of corruption in basic scientific researches; to define the place and role of fundamental scientific researches in knowledge-based economy taken as a whole, and Boston Chart, in particular.Methods. The methods involve the historical-philosophical and logical-linguistic analysis of texts; creation and studying of the elementary discrete mathematical model of the researched moral phenomenon at the level of artificial language of two-digit algebra of the natural right and morals; use of such conceptual and figurative tool of the economic theory as Boston Chart.Results and scientific novelty. The definition of the concept «basic scientific research» is given for the first time; the concept includes time parameter and knowledge of utility (the practical importance) of results of this research.Practical significance. The submitted definition (criterion) gives a possibility to establish at any moment of time definite borderline between the basic and the applied scientific search (the line undergoes change in the flow of time). The effective criterion of basic scientific researches offered by the author, and also exact specifying of their place and role in lifecycle of knowledge as goods in market economy (at the conceptual level of the Boston Chart) allow to designate an urgent problem of corruption of the scientific sphere in a new perspective. Along with some additional conditions, this new evidence could help to solve the problem.